2021
DOI: 10.3390/foods10020203
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bioactive Compounds from Pomegranate (Punica granatum L.) Peel Using Pressurized Liquid Extraction

Abstract: Pressurized liquid extraction (PLE) is a clean and environmentally friendly alternative for the recovery of bioactive compounds from fruit by-products. Herein we focused on PLE for the extraction of bioactive compounds from pomegranate peel using a combination of pressurized water and ethanol. The main aim was to determine the optimal PLE conditions, i.e., ethanol percentage and process temperature, to obtain a pomegranate peel extract (PPE) with maximum total phenolic content (TPC), punicalagin content, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…The suspension was sonicated twice in an ultrasonic bath at 59 kHz and 198 W for 30 s and magnetically stirred for two hours at room temperature. The insoluble fraction was removed after centrifugation at 2500 rpm for 15 min at 4 • C and resulted in about 55 wt% of the total weight of the sample and mainly consisted of fibers, proteins, and ash [30]. The collected supernatant was filtered (0.45 µm Sartorius filter), aliquoted (1 mL/vial), and stored at −20 • C for further analyses.…”
Section: Extraction Of Pomegranate Peel Powder Water-soluble Fraction...mentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension was sonicated twice in an ultrasonic bath at 59 kHz and 198 W for 30 s and magnetically stirred for two hours at room temperature. The insoluble fraction was removed after centrifugation at 2500 rpm for 15 min at 4 • C and resulted in about 55 wt% of the total weight of the sample and mainly consisted of fibers, proteins, and ash [30]. The collected supernatant was filtered (0.45 µm Sartorius filter), aliquoted (1 mL/vial), and stored at −20 • C for further analyses.…”
Section: Extraction Of Pomegranate Peel Powder Water-soluble Fraction...mentioning
confidence: 99%
“…To the purpose of identifying the molecules present in the PPP, an HPLC-ESI-TOF-MS measurement was performed, allowing the detection of a total of 17 phytochemical compounds (Figure 1 and Table 3). Twelve compounds, previously reported in pomegranate by-products [30], were classified according to their chemical nature in the following families: sugars, organic acids, phenolic acids, and hydrolysable tannins.…”
Section: Hplc-esi-tof-ms Analysismentioning
confidence: 99%
“…Pomegranate is consumed as fresh arils or as processed products, e.g., fresh or concentrated juice, infusions or jam. Nevertheless, juice yield is only the 40% of the whole fruit, and the remaining corresponds to pomegranate by-products considered wastes such as pomegranate peel (PP), seeds and mesocarp [2].…”
Section: Introductionmentioning
confidence: 99%
“…Pressurized liquid extraction (PLE) is a recent extraction method that has been widely used on seaweed, plants and food-related by-products [ 171 ], grape skin and seeds waste [ 172 ], passion fruit rinds [ 173 ], pomegranate peel [ 174 ], olive pomace [ 175 ], mulberry pulp [ 176 ], and beetroot waste [ 177 ]. Table 7 shows the optimum yield levels found in progress studies for the bioactive compounds found in FVW.…”
Section: Innovative Technologies Used For Bioactive Compound Extractionmentioning
confidence: 99%